The effect of replacing grains with quinoa on cardiometabolic risk factors and liver function in patients with non-alcoholic fatty liver: a randomized-controlled clinical trial - Gholamrezayi, Afsane; Hosseinpour-Niazi, Somayeh; Mirmiran, Parvin; Hekmatdoost, Azita (Frontiers in Nutrition, 2025)
PurposeQuinoa is a food containing dietary fiber and various phytochemicals with high nutritional value, which has a structure similar to whole grains. This randomized controlled trial aimed to assess the effect of substituting grains with quinoa on cardiovascular risk factors and liver function in individuals with Non-alcoholic fatty liver disease (NAFLD).MethodsForty-six participants were randomly assigned to either a control group, which maintained their regular grain-based diet, or an intervention group, where grains were replaced with quinoa for 12 weeks. Participants in the quinoa group were instructed to substitute grains with quinoa during lunch for 12 weeks. The primary outcome was to assess the changes in the Controlled Attenuation Parameter (CAP) score between the intervention and control groups. Secondary outcomes included the difference in cardiometabolic risk factors and liver function between the two groups.ResultsFollowing 12 weeks of intervention with quinoa, a significant reduction in weight, and waist circumferences (WC) were observed compared to the control group (p value < 0.05). Furthermore, even after adjustment for weight change, there was a significant reduction in CAP score, serum levels of low-density lipoprotein cholesterol (LDL-C), and an improvement in homeostatic model assessment for insulin resistance (HOMA-IR) in the quinoa group compared to the control group after the 12 weeks (p value < 0.05). However, no significant changes were observed in other measured parameters, including liver enzymes, fibroscan, fasting plasma glucose, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and inflammatory factors.ConclusionThis study demonstrated that replacing grains with quinoa led to a significant improvement in the CAP score, HOMA-IR, and LDL-C in individuals with NAFLD, regardless of any weight changes. Thus, incorporating quinoa—a plentiful and low-cost source of bioactive compounds—into the diets of NAFLS patients as a staple food could improve several cardiometabolic risk factors in these individuals.Clinical Trial RegistrationIRCT20100524004010N37.